ConfiYou : Sistem Pelatihan Keterampilan Presentasi dan Negosiasi Berbasis Virtual Reality untuk SDM UMKM - Razy, Fakhrul; Kamil Athallah, Aufa; Noor Prawita, Fat’hah (eProceedings of Applied Science, 2023)
Abstract—MSME entrepreneurs (Micro, Small and Medium Enterprises) have a product that continues to grow and is well known not only in remote parts of the country, but also in foreign countries. Because the products they have have a high enough appeal, many requests and orders are received from foreign countries. It is undeniable that some of these MSME entrepreneurs have difficulty in introducing and presenting their products, due to difficulties or lack of skill in using foreign languages, especially English. The ConfiYou application is a VR-based android application that aims to train users' English skills. In this application there will be 2 menu options, such as presentation & negotiation, later the user will present and introduce the product or business they have using Powerpoint. After making a presentation, there will be an audience who asks and the user will answer the question. After that has been passed, the training simulation will be completed and the results of the training simulation carried out by the user will appear.Keywords—MSME, presentation, negotiation, product